Mobile Computing : Technology , applications and service creation - Talukder, Asoke K | Hasn Ahmed | Roopa R Yavagal (New york.)
Mobile computing technology addresses challenges that enable the realization of a global village concept where people can seamlessly access any information anywhere anytime through any device.
Keywords: Mobile computing. Wireless communication systems